2011
DOI: 10.1103/physreva.83.013409
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the strong-field ionization ofN2andF2: A time-dependent density-functional-theory study

Abstract: We compare strong-field ionization probabilities of N 2 and F 2 molecules using time-dependent density functional theory calculations. Accurate nuclear potentials and ground vibrational wave functions are incorporated into our study. For both molecules, the effect of molecular vibration is small, while that of the molecular orientation is significant. When compared to the ionization probability of a molecule at the equilibrium geometry, we estimate the effect of the ground state vibration to be within 3% for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…An important question, however, is: What makes the HOMO (3σ g ) atomic-like? An earlier study of ours showed that the projection of the outer region of the 3σ g orbital is 82.7% s and 17.1% d z 2 [27]. This ratio varies with the radius r. Dipole matrix elements involving the d z 2 orbital depend on the orientation.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…An important question, however, is: What makes the HOMO (3σ g ) atomic-like? An earlier study of ours showed that the projection of the outer region of the 3σ g orbital is 82.7% s and 17.1% d z 2 [27]. This ratio varies with the radius r. Dipole matrix elements involving the d z 2 orbital depend on the orientation.…”
Section: Introductionmentioning
confidence: 63%
“…Later this work was extended to treat arbitrary polarization directions for the study of the anisotropy of ionization and HHG [27,33,34]. We use the approach of Ref.…”
Section: Time-dependent Density Functional Theory For Molecules Imentioning
confidence: 99%
See 1 more Smart Citation
“…The quantum action A[ ] has a stationary point at the TD density of the system, and hence from the Euler equation we get the working equations [20,21]. When we project Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate calculations of ionization probability for a fixed laser intensity can be accomplished by solving the timedependent Schrödinger equation (TDSE) for atoms and some small molecules [8][9][10][11][12][13][14][15][16][17][18][19], mostly based on the single-activeelectron (SAE) model. Calculations including all electrons in the atom or molecules have been used within the timedependent density functional theory (TDDFT) [20][21][22][23][24][25], the time-dependent Hartree-Fock (TDHF) theory [26,27], or the multiconfiguration time-dependent Hartree-Fock (MCTDHF) theory [28][29][30]. These calculations are very time-consuming and their accuracy is also difficult to judge.…”
Section: Introductionmentioning
confidence: 99%